Automatic coronary artery detection in echocardiogram image - Ramadan Humada, Esmael Ali (2007)
This paper presents a technique to automatically detect the area of the wall of the coronary artery in an echocardiogram image that separates the left and right chambers of the heart. This detection is crucial for further analysis of the heart such as the detection of myocardium infarction. We propose a twostage approach that consists of the pre-processing stage and the decision stage. The pre-processing stage involves common image processing strategies while the decision stage involves the extraction and calculation of two feature ratios to finally determine the region of interest. Our proposed technique shows a performance ofat least 90% accuracy.